Preparation and physicochemical characterization of fish skin gelatine hydrolysate from shortfin scad (Decapterus macrosoma) - H. I. Rasli (2021)
Enzymatic hydrolysis of proteins is an important bioprocess method to prepare bioactive peptides with many functionality and health benefits. The aims of the present work were to prepare and determine the physicochemical characteristics of gelatine hydrolysate from skin of shortfin scad (SSGH) via hydrolysis using alcalase. Analyses on chemical composition, molecular weight by SDS PAGE, protein concentration, amino acid composition, Fourier Transform Infrared Spectroscopic features, and solubility of SSGH were thus performed. The yield of SSGH obtained was 51.01% (d.b.). The chemical compositions of SSGH for moisture, protein, fat, and ash were 13.82%, 90.05%, 1.95%, and 12.48%, respectively. SSGH showed low molecular weight (<17 kDa) with a protein concentration of 33.53 mg/mL. Amino acid composition of SSGH contained high amount of glycine, proline, glutamic acid, alanine and arginine with a total content of essential amino acids of 10.74%. The solubility of SSG and SSGH were higher at pH 10, and amide I, II, III, A and B were found in both SSG and SSGH.